2014
DOI: 10.1183/09031936.00151014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of physical activity in COPD outcomes: moving forward

Abstract: @ERSpublications From observational studies, it is now clear that physical inactivity is linked with poor outcome in COPD http://ow.ly/AJ7mFArguably, three outcome categories are of greatest importance to chronic obstructive pulmonary disease (COPD) patients, their families and their caregivers: health-related quality of life (including symptom burden); hospitalisations and other forms of healthcare utilisation; and, of course, mortality. Lower levels of baseline physical activity are not only prevalent in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…12 Previous studies have shown that physical inactivity leads to a higher risk of hospitalizations, exacerbations and mortality and a reduced healthrelated quality of life in COPD patients, although the exact relationship between various clinical and functional indicators and physical activity is not yet elucidated. [13][14][15] In consequence, increasing physical activity has the potential of being one key nonpharmacological interventions in COPD patients, irrespective of the specific ABCD group. 1 In Romania, the respiratory symptoms (RS) were explored in several national COPD awareness campaigns that showed an increasing prevalence of lung function impairment.…”
Section: Introductionmentioning
confidence: 99%
“…12 Previous studies have shown that physical inactivity leads to a higher risk of hospitalizations, exacerbations and mortality and a reduced healthrelated quality of life in COPD patients, although the exact relationship between various clinical and functional indicators and physical activity is not yet elucidated. [13][14][15] In consequence, increasing physical activity has the potential of being one key nonpharmacological interventions in COPD patients, irrespective of the specific ABCD group. 1 In Romania, the respiratory symptoms (RS) were explored in several national COPD awareness campaigns that showed an increasing prevalence of lung function impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, it is incompletely understood why patients with COPD are inactive. [4,5] Defining patient characteristics that are associated with physical inactivity is important for the development of targeted interventions, also for COPD patients with mild or moderate airflow obstruction. The decline in physical activity already starts in mild disease stages, [5][6][7][8] even before the physician diagnosis of COPD is made.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based data demonstrate that as little as 2 h of activity per week, either walking or cycling, can have significant positive effects on the course of COPD [11]. Conversely, physical inactivity is a major-indeed, perhaps the strongest-risk factor for poor outcomes in patients with COPD [12]. As well as its association with breathlessness, physical inactivity is also linked to an increased risk of exacerbations, hospitalisations and mortality [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%